MANAJEMEN KURIKULUM PONDOK PESANTREN DALAM MENINGKATKAN KUALITAS PENDIDIKAN KARAKTER (STUDI PONDOK PESANTREN MUKHTAR SYAFA’AT MESUJI OKI) - PIRKUN (IAI Darussalam, 2022)
Improving the quality of character education for students is not an easy job, where students who are used to a free life tend to find it difficult to adapt to an environment full of rules, so good curriculum management is needed to improve character education. This study aims to analyze the implementation of Islamic boarding school curriculum management, and efforts to improve the character education of students at the Mukhtar Syafa'at Mesuji OKI Islamic boarding school. This study applies qualitative research in the form of a case study. The result is that the management of the pesantren curriculum cannot be separated from the management functions known as POAC namely planning, organizing, actuating, controlling, where the four functions are popularized by the terms planning, organizing, implementing, and evaluating. These four functions have been carried out at the Mukhtar Syafa'at Mesuji OKI Islamic boarding school. Furthermore, in an effort to improve character education at the Mukhtar Syafa'at Mesuji OKI Islamic Boarding School, a competition and competency program was carried out. The implication is that this character is expected to become a provision for the students when the students are no longer in the boarding school environment and are no longer in the family environment when they are adults.